A Quadrupolar Bis‐Triarylborane Chromophore as a Fluorimetric and Chirooptic Probe for Simultaneous and Selective Sensing of DNA, RNA and Proteins. Issue 10 (28th January 2020) - Ban, Željka; Griesbeck, Stefanie; Tomić, Sanja; Nitsch, Jörn; Marder, Todd B.; Piantanida, Ivo
Abstract: Invited for the cover of this issue are the groups of Todd B. Marder at the Julius‐Maximilians‐Universität Würzburg and Ivo Piantanida at the Ruder Boškovic Institute. The image depicts the molecular structure of a bis‐triarylborane‐based chromophore that is simultaneously detecting ds‐DNA and proteins. Read the full text of the article at 10.1002/chem.201903936 . Abstract : " We are working to devise dual‐method multipurpose probes which will again bind to multiple bio‐relevant targets (DNA, RNA, proteins) yielding different signals for each target, not only by fluorescence but also by other, independent bio‐applicable spectroscopic methods " Read more about the story behind the cover in the Cover Profile and about the research itself on page 2195 ff. (DOI: 10.1002/chem.201903936 ).